Overexpression of rice serotonin N‐acetyltransferase 1 in transgenic rice plants confers resistance to cadmium and senescence and increases grain yield. Issue 3 (1st March 2017) - Lee, Kyungjin; Back, Kyoungwhan
Abstract: While ectopic overexpression of serotonin N ‐acetyltransferase ( SNAT ) in plants has been accomplished using animal SNAT genes, ectopic overexpression of plant SNAT genes in plants has not been investigated. Because the plant SNAT protein differs from that of animals in its subcellular localization and enzyme kinetics, its ectopic overexpression in plants would be expected to give outcomes distinct from those observed from overexpression of animal SNAT genes in transgenic plants. Consistent with our expectations, we found that transgenic rice plants overexpressing rice ( Oryza sativa ) SNAT1 ( OsSNAT1 ) did not show enhanced seedling growth like that observed in ovine SNAT ‐overexpressing transgenic rice plants, although both types of plants exhibited increased melatonin levels. OsSNAT1 ‐overexpressing rice plants did show significant resistance to cadmium and senescence stresses relative to wild‐type controls. In contrast to tomato, melatonin synthesis in rice seedlings was not induced by selenium and OsSNAT1 transgenic rice plants did not show tolerance to selenium. T2 homozygous OsSNAT1 transgenic rice plants exhibited increased grain yield due to increased panicle number per plant under paddy field conditions. These benefits conferred by ectopic overexpression of OsSNAT1 had not been observed in transgenic rice plants overexpressing ovine SNAT, suggesting that plant SNAT functions differently from animal SNAT in plants.